(untitled) (EAAE Annual Conference Proceedings, 2023)
The issues raised within the New European Bauhaus directly point to the question of the collective, both as a spatial as well as a social notion. In its physical manifestation, the spatial imprint of collectivity has a direct relation to the cultural and climactic context. While many implications of answering these issues can be shared regardless of geographical position, when talking about the physical framing of collectivity we can find common denominators among countries in southern Europe, in their traditions, way of life, relationship to open space, but also challenges facing urban expansion, heat islands, pollution, contemporary and active approaches to heritage etc.